2020
DOI: 10.1021/acsami.0c15836
|View full text |Cite
|
Sign up to set email alerts
|

Cyclodextrin Porous Liquid Materials for Efficient Chiral Recognition and Separation of Nucleosides

Abstract: Porous liquids are porous materials that have exhibited unique properties in various fields. Herein, we developed a method to synthesize the type I porous liquids via liquefaction of cyclodextrins by chemical modification. The cyclodextrin porous liquids were characterized by Fourier-transform infrared (FTIR) spectroscopy, NMR, matrix-assisted laser desorption ionization-time-of-flight mass spectrometry (MALDI-TOF MS), circular dichroism (CD), and UV−vis spectroscopy. The measured ionic conductivity of the γ-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(35 citation statements)
references
References 76 publications
1
34
0
Order By: Relevance
“…Before this, the previous review from Dai et al has stated that PLs can be used as a platform for novel chromatography columns. [17] This has been verified by the recent study of Wang et al [57] (Figure 24a,b). In this work, through liquefaction of cyclodextrins by chemical modification, a Type I PL was successfully prepared toward pyrimidine nucleosides separation in water.…”
Section: Chiral Separationsupporting
confidence: 78%
See 3 more Smart Citations
“…Before this, the previous review from Dai et al has stated that PLs can be used as a platform for novel chromatography columns. [17] This has been verified by the recent study of Wang et al [57] (Figure 24a,b). In this work, through liquefaction of cyclodextrins by chemical modification, a Type I PL was successfully prepared toward pyrimidine nucleosides separation in water.…”
Section: Chiral Separationsupporting
confidence: 78%
“…Therefore, a homogeneous and stable UiO-66-OH PL with superior flowing ability at room temperature was obtained. In another study, Wang et al [57] prepared a Type 1 cyclodextrin PL via liquefaction of cyclodextrins (Figure 14b). In this paper, the cyclodextrins-based (α-CD, β-CD, and γ-CD) PLs were prepared via the reaction of imidazole-1-acetic chloride with γ-cyclodextrin in the presence of triethylamine.…”
Section: Direct Covalent Postsynthetic Modificationmentioning
confidence: 99%
See 2 more Smart Citations
“…Porous liquids consisting of molecular cages thereby exhibit host-guest properties, as exempli ed by the shape and size selectivity for a series of isomeric alcohols in Type I porous ionic liquids composed of tetrahedral coordination cage 4 . Most recently, Xia et al reported the use of the cyclodextrin-derived Type-I porous liquid for the e cient chiral recognition and separation of nucleosides in the solution 36 . Except for the two examples above, current research on the host-guest properties of the molecular cage-based porous liquids has been mainly focused on the accommodation of small gaseous molecules such as carbon dioxide 8,37,38 , methane 11,14,39 and chloro uorocarbon 4 .…”
Section: Introductionmentioning
confidence: 99%